THE INFLUENCE OF PRINCIPAL COMPENSATION AND LEADERSHIP ON TEACHER PERFORMANCE AT STATE 5 JUNIOR HIGH SCHOOL (SMP) HIGH CLUB CITY WITH WORK MOTIVATION AS INTERVENING VARIABLES - CAHYADI, WILLY (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to determine the effect of compensation and leadership on teacher performance through work motivation as an intervening variable at SMP Negeri 5 Tebing Tinggi. The research method used is a quantitative method using SPSS version 25.00. The data collected from the results of distributing questionnaires to teachers of SMPN 5 Tebing Tinggi were 39 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination (R2) analysis, hypothesis testing, namely T test and path analysis. The results of SPSS in this study are the Leadership variable (X1) has no effect on the work motivation variable (Z),